2012
DOI: 10.1177/1078345811435767
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia and Gonorrhea Screening Using Urine-Based Nucleic Acid Amplification Testing Among Males Entering New York City Jails

Abstract: This article describes a pilot screening program to detect Chlamydia trachomatis (Ct) and Neisseria gonorrhoeae (Ng) sexually transmitted infections (STIs) in adolescent and adult males newly incarcerated in New York City jails using urine-based nucleic acid amplification technology (NAAT). Between December 8 and 22, 2003, 2,417 males were tested; 162 (6.7%) were found positive for Ct and/or Ng STIs, with 138 (86.8%) exhibiting no STI signs or symptoms and 102 (63%) treated prior to jail release. Younger age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Opt-out testing was only described in studies conducted outside the EU/EEA and exclusively as a modality for HIV active case finding ( 13 , 29 ). Client-initiated testing was described as a complementary approach to opt-in offered during imprisonment for HIV ( 47 , 53 ) or reported as comparator in a few additional studies investigating the effect of different testing modalities for HCV ( 35 , 45 ), HIV ( 13 ), and STIs ( 31 , 85 89 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opt-out testing was only described in studies conducted outside the EU/EEA and exclusively as a modality for HIV active case finding ( 13 , 29 ). Client-initiated testing was described as a complementary approach to opt-in offered during imprisonment for HIV ( 47 , 53 ) or reported as comparator in a few additional studies investigating the effect of different testing modalities for HCV ( 35 , 45 ), HIV ( 13 ), and STIs ( 31 , 85 89 ).…”
Section: Resultsmentioning
confidence: 99%
“…Testing-results notification was mainly reported for HIV, and this frequently was high as 100% at least for HIV-positive individuals ( 13 , 42 , 49 , 84 ). In 15 studies, researchers reported on treatment initiation after diagnosis for HIV ( 46 , 60 , 64 , 68 ), STIs ( 31 , 46 , 54 , 56 , 85 , 90 ), and TB ( 57 , 70 – 72 , 100 ). The reported rates were variable (23%–100%), with treatment rates for LTBI being at the lower end of the range (23%–58%), whereas treatment ranges for active TB were higher (87%–100%).…”
Section: Resultsmentioning
confidence: 99%
“…1 Several studies show that individuals entering jail have a high prevalence of sexually transmitted infections (STI) 24 ; however, there are few data on STI positivity among this population following release. Given the current limitations of jail-based STI services, 5 it is likely that a portion of STI positivity in the post-incarceration period reflects untreated or undiagnosed STI acquired prior to or during incarceration as well as STI acquired post-release.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, ever-incarcerated people have higher rates of HIV, sexually transmitted infections (STIs), tuberculosis (TB), and all-cause mortality compared with the general population (Baillargeon & Bradshaw, 2003; Binswanger et al, 2007; Hammett, Harmon, & Rhodes, 2002; Massoglia, 2008; Mertz, Voigt, Hutchins, Levine, & the Jail STD Prevalence Monitoring Group, 2002; National Commission on Correctional Health Care, 2002; White et al, 2001). Ever-incarcerated individuals often report behaviors associated with increased morbidity and mortality, such as having multiple sex partners and unprotected sex, intravenous drug use, and being homeless (Begier et al, 2010; Franklin, Kaytal, Mahajan, & Parvez, 2012; Parvez, Kaytal, Alper, Leibowitz, & Venters, 2013). Risk taking behaviors upon release from incarceration may contribute to disease transmission during the community reentry period (Morrow, Eldridge, Nealey-Moore, Grinstead, & The Project START Study Group, 2007), along with an increased risk of death often related to drug use after a period of abstinence (Binswanger et al, 2007; Lim et al, 2012; Rosen, Schoenbach, & Wohl, 2008).…”
Section: Introductionmentioning
confidence: 99%